2018
DOI: 10.1038/s41593-018-0110-8
|View full text |Cite|
|
Sign up to set email alerts
|

Social deficits in Shank3-deficient mouse models of autism are rescued by histone deacetylase (HDAC) inhibition

Abstract: Haploinsufficiency of the SHANK3 gene is causally linked to autism spectrum disorder (ASD), and ASD-associated genes are also enriched for chromatin remodelers. Here, we found that brief treatment with romidepsin, a highly potent class I histone deacetylase (HDAC) inhibitor, alleviated social deficits in Shank3-deficient mice, which persisted for ~3 weeks. HDAC2 transcription was upregulated in these mice, and knockdown of HDAC2 in prefrontal cortex also rescued their social deficits. Nuclear localization of β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
205
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(228 citation statements)
references
References 46 publications
(77 reference statements)
17
205
1
1
Order By: Relevance
“…For example, Duffney et al, (2015) recently demonstrated that reduced social preference in Shank3 +/ΔC mice is associated with diminished NMDA receptor function and distribution in prefrontal regions. In the same mouse model, social deficits were ameliorated by treatment with a histone deacetylase (HDAC) inhibitor, highlighting a contribution of epigenetic mechanisms to the expression of social deficits in Shank3-deficiency (Qin et al, 2018). Our results are in keeping with these observations, and suggest that the prefrontal dysfunction that characterizes SHANK3-deficient mice affects complex socio-communicative behavior via a large-scale involvement of distributed fronto-striatal and fronto-cortical substrates.…”
Section: Discussionsupporting
confidence: 82%
“…For example, Duffney et al, (2015) recently demonstrated that reduced social preference in Shank3 +/ΔC mice is associated with diminished NMDA receptor function and distribution in prefrontal regions. In the same mouse model, social deficits were ameliorated by treatment with a histone deacetylase (HDAC) inhibitor, highlighting a contribution of epigenetic mechanisms to the expression of social deficits in Shank3-deficiency (Qin et al, 2018). Our results are in keeping with these observations, and suggest that the prefrontal dysfunction that characterizes SHANK3-deficient mice affects complex socio-communicative behavior via a large-scale involvement of distributed fronto-striatal and fronto-cortical substrates.…”
Section: Discussionsupporting
confidence: 82%
“…Histone deacetylase activity, GPCR signaling, proteasome function, MYC targets, and cell cycle processes are representative examples. Some of the enumerated biological functions have previously been related to both ASD and cancer(5964). These abnormalities could help explain putative inverse comorbid associations between ASD and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Effect on the morphology of dendritic spine and synaptic transmission Expression of SHANK3 was strongly regulated by methylated CpG island. [195,196] Histone modification…”
Section: Shank3mentioning
confidence: 99%